2014
DOI: 10.1002/mnfr.201400307
|View full text |Cite
|
Sign up to set email alerts
|

Betaine recovers hypothalamic neural injury by inhibiting astrogliosis and inflammation in fructose‐fed rats

Abstract: These findings suggest that betaine inhibits fructose-caused astrogliosis and inflammation by the suppression of TLR4/NF-κB pathway activation and HDAC3 expression to protect against hypothalamic neural injury, which, at least partly, contributes to the improvement of fructose-induced metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 63 publications
(80 reference statements)
0
39
0
Order By: Relevance
“…Data on stress-related perturbations in the hypothalamic inflammatory status are rather conflicting, as the expression of proinflammatory cytokines has been reported to be elevated [27] or unchanged [28] in male rats after chronic stress. As for nutrients, a high-fat diet has been predominantly described to induce obesity-related hypothalamic inflammation [50], though fructose overconsumption also has a potential to activate the NFκB signaling pathway [2, 26]. However, most in vivo studies describing fructose-related neuroinflammation, also reported increased fat mass and a disturbed lipid status in the form of elevated plasma triglycerides and free fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on stress-related perturbations in the hypothalamic inflammatory status are rather conflicting, as the expression of proinflammatory cytokines has been reported to be elevated [27] or unchanged [28] in male rats after chronic stress. As for nutrients, a high-fat diet has been predominantly described to induce obesity-related hypothalamic inflammation [50], though fructose overconsumption also has a potential to activate the NFκB signaling pathway [2, 26]. However, most in vivo studies describing fructose-related neuroinflammation, also reported increased fat mass and a disturbed lipid status in the form of elevated plasma triglycerides and free fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that the proinflammatory cytokines IL-1β [24] and TNFα [25] can induce inhibitory phosphorylation of insulin receptor substrate 1 (IRS1) on the Ser 307 residue (pIRS1-Ser 307 ), inhibiting kinase activity of the insulin receptor. High fructose consumption has a potential to activate the nuclear factor-κB (NFκB) signaling pathway in the hypothalamus elevating proinflammatory cytokines [2, 26]. On the other hand, data on stress-related perturbations in the hypothalamic inflammatory status are rather conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Fructose induces hypothalamic astrogliosis both in vivo and in vitro (Li et al 2014). On the contrary, although high sucrose intake induces hypothalamic inflammation, this was not found to be associated with astrogliosis (FuenteMartin et al 2013).…”
Section: R62mentioning
confidence: 99%
“…All the histological protocols were in accordance with the standard procedures demonstrated previously. 34 . The sequences used in this study are shown in Table 1.…”
Section: Histological Analysismentioning
confidence: 99%